Blockchain Technology Integration in Distributed Healthcare Systems: A Technical Analysis - Brahmanand Reddy Bhavanam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the integration of blockchain technology in distributed healthcare systems, focusing on its transformative potential in addressing critical challenges in healthcare data management, security, and interoperability. The article presents a comprehensive examination of blockchain architecture, implementation strategies, and practical applications in healthcare settings, including electronic health records management, clinical trials, pharmaceutical supply chain, and patient consent management. Through detailed analysis of security frameworks, privacy mechanisms, and compliance requirements, the article demonstrates how blockchain technology enhances data protection while maintaining operational efficiency. The investigation extends to performance metrics, comparing traditional and blockchain-based healthcare systems across multiple parameters, including data synchronization, system availability, and cost-effectiveness. The article also explores emerging challenges and future directions, particularly in areas of scalability, integration with IoMT devices, and cross-border data sharing. This article provides valuable insights for healthcare organizations considering blockchain adoption, offering implementation guidelines and recommendations for sustainable integration of blockchain technology in healthcare environments.